Chemical Composition and Cytotoxic Activity of Chenopodium ambrosioides L. Essential Oil from Togo - Koba, Koffi; Catherine, Guyon; Raynaud, Christine; Chaumont, Jean-Pierre; Sanda, Komla; Laurence, Nicod (Bangladesh Journal of Scientific and Industrial Research, 2010)
The leaf essential oil of Chromolaena odorata L. (Chenopodiaceae) from Togo were steam-distilled, analyzed by GC and GC-MS for chemical composition and investigated in vitro for its potential cytotoxic activity on human epidermic cell line HaCat. The chemical composition showed that the main constituents of essential oil sample were respectively ascaridole (51.12 %), p-cymene (19.88 %), neral (8.70%) and geraniol (7.55%). The in vitro cytotoxicity bioassays on human cell line HaCaT revealed moderate toxicity level of C. ambrosioides essential oil IC50 with 700 μL.mL-1. Pure commercial neral standard showed high toxicity with IC50 value of 100 μL.mL-1). Conversely, pure ascaridole p-cymene and geraniol standards appeared almost non-toxic (IC50 >1000 μL.mL-1), proving the major role played by neral in the overall toxicity showed by the C. ambrosiodes oil sample tested in this work. Keywords: Chenopodium ambrosioides; Essential oil; Ascaridole; p-cymene; HaCaT cell line; Cytotoxicity. DOI: 10.3329/bjsir.v44i4.4594 Bangladesh J. Sci. Ind. Res. 44(4), 435-440, 2009